PENGARUH PENGGUNAAN MEDIA KOMIK TERHADAP KEMAMPUAN MENGANALISIS PENOKOHAN DALAM VERITA FANTASI PADA SISWA KELAS VII SMP NEGERI 15 KENDARI - Wa Ode Nurhijrah; Fahruddin; La Yani Konisi (Jurnal Bastra (Bahasa dan Sastra), 2025)
This study aims to identify the influence of the use of comic media on the ability to analyze characters in fantasy stories in grade VII students of SMP Negeri 15 Kendari. In this study, the ex post facto method and sample drawing technique were used, namely Proportionate Stratified Random Sampling. The instruments used are questionnaires and written tests. Based on the results of the analysis of the research data, it is known that there is a significant positive influence between the use of Comic Media on learning outcomes in the form of the Ability to Analyze Characters in Fantasy Stories of grade VII students of SMP Negeri 15 Kendari. The results of the hypothesis test show that the significance value (Sig.) is 0.002. When compared to the value of α = 0.05, then 0.002 < 0.05, which means that H0 is rejected and Ha is accepted. If viewed from the tcount value, a value of 3.157 > ttable 1.985 is obtained, which means ha is accepted and h0 is rejected so it can be concluded that the variable of influence on the use of comic media (X) affects the variable of learning outcomes (Y). This can also be seen from the results of the determination coefficient test which revealed the contribution of the Use of Comic Media of 9.5%. Although the contribution given is still very low, if the learning process that takes place is further improved by paying attention to various factors that can affect students' analytical skills, the influence on learning outcomes can increase.